An open-label, randomised study of dihydroartemisinin-piperaquine versus artesunate-mefloquine for falciparum malaria in Asia. - Valecha, N; Phyo, A; Mayxay, M; Newton, P; Krudsood, S; Keomany, S; Khanthavong, M; Pongvongsa, T; Ruangveerayuth, R; Uthaisil, C; Ubben, D; Duparc, S; et al. (Public Library of Science, 2010)
BACKGROUND: The artemisinin-based combination treatment (ACT) of dihydroartemisinin (DHA) and piperaquine (PQP) is a promising novel anti-malarial drug effective against multi-drug resistant falciparum malaria. The aim of this study was to show non-inferiority of DHA/PQP vs. artesunate-mefloquine (AS+MQ) in Asia. METHODS AND FINDINGS: This was an open-label, randomised, non-inferiority, 63-day follow-up study conducted in Thailand, Laos and India. Patients aged 3 months to 65 years with Plasmodium falciparum mono-infection or mixed infection were randomised with an allocation ratio of 2:1 to a fixed-dose DHA/PQP combination tablet (adults: 40 mg/320 mg; children: 20 mg/160 [DOSAGE ERROR CORRECTED] mg; n = 769) or loose combination of AS+MQ (AS: 50 mg, MQ: 250 mg; n = 381). The cumulative doses of study treatment over the 3 days were of about 6.75 mg/kg of DHA and 54 mg/kg of PQP and about 12 mg/kg of AS and 25 mg/kg of MQ. Doses were rounded up to the nearest half tablet. The primary endpoint was day-63 polymerase chain reaction (PCR) genotype-corrected cure rate. Results were 87.9% for DHA/PQP and 86.6% for AS+MQ in the intention-to-treat (ITT; 97.5% one-sided confidence interval, CI: >-2.87%), and 98.7% and 97.0%, respectively, in the per protocol population (97.5% CI: >-0.39%). No country effect was observed. Kaplan-Meier estimates of proportions of patients with new infections on day 63 (secondary endpoint) were significantly lower for DHA/PQP than AS+MQ: 22.7% versus 30.3% (p = 0.0042; ITT). Overall gametocyte prevalence (days 7 to 63; secondary endpoint), measured as person-gametocyte-weeks, was significantly higher for DHA/PQP than AS+MQ (10.15% versus 4.88%; p = 0.003; ITT). Fifteen serious adverse events were reported, 12 (1.6%) in DHA/PQP and three (0.8%) in AS+MQ, among which six (0.8%) were considered related to DHA/PQP and three (0.8%) to AS+MQ. CONCLUSIONS: DHA/PQP was a highly efficacious drug for P. falciparum malaria in areas where multidrug parasites are prevalent. The DHA/PQP combination can play an important role in the first-line treatment of uncomplicated falciparum malaria. TRIAL REGISTRATION: Controlled-Trials.com ISRCTN81306618.